A Review on Different Kinds of Artificial Intelligence Solutions in TCM Syndrome Differentiation Application. (9th March 2021) - Song, Yujuan; Zhao, Bin; Jia, Jun; Wang, Xuebing; Xu, Sibai; Li, Zhenjing; Fang, Xu
Abstract : In 1979, the first computer program for TCM diagnosis was launched, although this time was about 30 years after artificial intelligence (AI) came into being and began to be widely used. However, an endless stream of artificial intelligence methods was applied in the field of Chinese medicine research, expert system, artificial neural network, data mining, and multivariate analysis; not limited to what was mentioned, this study tried to make a review on application of AI to TCM syndrome differentiation, while summarizing the artificial intelligence application of TCM syndrome differentiation in the current context. It also provides a theoretical background for the upcoming fully automated research on TCM syndrome differentiation and diagnosis robot.